2014
DOI: 10.1016/j.sbspro.2014.10.313
|View full text |Cite
|
Sign up to set email alerts
|

Immediacy Gratification in Online News Consumption and its Relations to Surveillance, Orientation and Elaboration of News

Abstract: Increasing numbers of people read newspapers online. This study uses argument about reform proposed in the theory of remediation to explain the shift from traditional print to online news sources. The argument pivots around the idea that the new media improves upon the inadequacies of older media. The improvement is manifested in the striving for "immediacy" which remediation theory considers the "goal" of media. Blending the theory of remediation and the uses and gratifications approach, this study proposes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Information surveillance is considered as the most significant factor to determine the actual media usage of individuals. Research has verified several motives to explain the pattern of media usage among individuals (Omar, 2014). One of the utmost shared motives is information surveillance (e.g., Jensen, 2011).…”
Section: Information Surveillancementioning
confidence: 99%
“…Information surveillance is considered as the most significant factor to determine the actual media usage of individuals. Research has verified several motives to explain the pattern of media usage among individuals (Omar, 2014). One of the utmost shared motives is information surveillance (e.g., Jensen, 2011).…”
Section: Information Surveillancementioning
confidence: 99%
“…However, since the user of the Internet has risen nowadays, online news has become the mainstream news medium nowadays, even some issues need to be considered, like reliability and credibility. It appears that since there is no gatekeeper in online media, the source of this media still be questioned in the reliability and credibility (Nguyen in Omar, 2014;Wilson et al, 2011). On the other side, online news became prominent nowadays in term of the democracy practice in a country, such as Indonesia (Hill & Sen, 2007;Hill, 2003), Singapore (Rodan, 2011), and Malaysia (Willnat et al, 2013;Rajaratnam, 2009).…”
Section: B Online News Site Mediamentioning
confidence: 99%
“…Studies of youth media usage have found that they use the Internet for many activities, including social networking, playing games, watching films and videos, searching for information, exchanging instant messages, listening to music and catching up on the news (Vahlberg, 2010;Lee and Ma, 2012). Similarly, in Malaysia, youth are the greatest consumers of new media as they use them for communication, information seeking and entertainment (Omar, 2014;Shin and Ismail, 2014). As they divide their time among many things simultaneously on multiple online platforms, scholars are concerned about the limited time they have for news consumption (Lee and Leung, 2008;De Waal and Schoenbach, 2010).…”
Section: Introductionmentioning
confidence: 99%